2019
DOI: 10.1186/s13244-019-0752-4
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the axial skeleton in spondyloarthritis: the many faces of new bone formation

Abstract: Spondyloarthritis has two hallmark features: active inflammation and structural lesions with new bone formation. MRI is well suited to assess active inflammation, but there is increasing interest in the role of structural lesions at MRI. Recent MRI studies have examined the established features of new bone formation and demonstrated some novel features which show diagnostic value and might even have potential as possible markers of disease progression. Although MRI is not the first imaging modality that comes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A multivariate analysis of new bone formation in ankylosing spondylitis (AS) showed that fat metaplasia and backfill were significantly correlated with ankylosis ( 14 ). Typically, backfill indicates the initiation of new bone formation ( 1 ). However, no study has explored the correlation between fat metaplasia and backfill.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A multivariate analysis of new bone formation in ankylosing spondylitis (AS) showed that fat metaplasia and backfill were significantly correlated with ankylosis ( 14 ). Typically, backfill indicates the initiation of new bone formation ( 1 ). However, no study has explored the correlation between fat metaplasia and backfill.…”
Section: Discussionmentioning
confidence: 99%
“…Axial spondyloarthritis (axSpA) is a chronic inflammatory rheumatic disease affecting the spine and the sacroiliac (SI) joints. The prominent feature of axSpA in the new bone formation is ankylosis in the SI joints and bridging syndesmophytes in the spine ( 1 ). This feature is associated with irreversible spinal immobility and functional limitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI can detect early changes in spondyloarthritis, revealing subtle erosions, bone edema, and signs of inflammation. Another hallmark feature of AxSpA that has been well documented is structural lesions with new bone formation [13]. This can be assessed on MRI, and early signs of bone formation can help lead to the diagnosis of AxSpa.…”
Section: Discussionmentioning
confidence: 99%
“…formation can form not only in the sacroiliac joints but also in the manubriosternal joint potentially impacting chest wall movement. Findings of bone formation can also be helpful in monitoring disease progression [13]. Early evaluation and diagnosis of spondyloarthritis can lead to earlier initiation of treatment with both pharmacologic and nonpharmacologic interventions.…”
Section: Discussionmentioning
confidence: 99%